2019
DOI: 10.4236/ape.2019.94021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Teaching Style on Pupils Engagement in Physical and Sport Education in Grammar School of Brazzaville

Abstract: The aim of the study is to analyze whether the teaching style in Physical and Sport Education (PSE) influences the involvement of students in learning. The theory that non-interference, democratic and authoritarian styles of teaching at different times in the same physical and sport education lessons promotes student engagement in the building of motor skills. Our study took place in Brazzaville in public grammar school. A sample of 20 Physical and sport education teachers and 321 grade 4 and 3 students took p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been reported that most Chinese undergraduates cannot even do ten push-ups. erefore, Physical Education (PE) is attracting the attention of the government and people from all walks of life [1]. In particular, CAI is a vivid and flexible new teaching concept based on the foundation of the current information age, namely, the computer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that most Chinese undergraduates cannot even do ten push-ups. erefore, Physical Education (PE) is attracting the attention of the government and people from all walks of life [1]. In particular, CAI is a vivid and flexible new teaching concept based on the foundation of the current information age, namely, the computer.…”
Section: Introductionmentioning
confidence: 99%